Immersive virtual reality for acupuncture knowledge and practical skills: a comparative educational study - Lingyi Wu; Vigneshkumar Chellappa; Qi Xie; Xuan Mao; Yan Luximon; Riji Yu (Frontiers in Public Health, 2026)
Background Acupuncture education requires mastery of complex theoretical concepts and psychomotor skills, yet conventional teaching often struggles to bridge the gap between abstract knowledge and hands-on application. This study evaluated the association of an immersive virtual reality-based acupuncture training system, PainEaseVR, with posttest learning outcomes when used as a supplement to conventional acupuncture education. Methods A stratified, randomized, posttest comparison study was conducted with 60 third-year undergraduate students majoring in Traditional Chinese Medicine. Participants were assigned to either an experimental group using PainEaseVR ( n = 30) or a control group receiving conventional instruction ( n = 30). Both groups completed 12 h of instruction, including 6 h of theoretical teaching and 6 h of practical training. Learning outcomes were assessed using a 12-item theoretical knowledge test, an 18-indicator practical skills assessment, and an 11-item student feedback questionnaire. Results The VR group achieved higher scores in theoretical knowledge (M = 10.08, SD = 0.99) than the traditional group (M = 9.04, SD = 1.31). The VR group also outperformed the traditional group in practical skills (M = 32.52, SD = 2.28 vs. M = 28.62, SD = 2.77). Students in the VR group reported higher satisfaction, engagement, and confidence across all feedback items. Conclusion PainEaseVR appears to be a promising supplementary tool for acupuncture education. The findings suggest that VR was associated with higher scores in acupuncture knowledge and practical skills, as well as a more engaging learning experience, within the context of this posttest comparison study.